Decreased risk of breast cancer associated with oral bisphosphonate therapy - Mathew A (Dove Medical Press, 2012)
Aju Mathew,1 Adam Brufsky,21Department of Internal Medicine, University of Pittsburgh Medical Center, 2Division of Hematology/Oncology, Magee-Womens Hospital, University of Pittsburgh Cancer Institute, Pittsburgh, PA, USAAbstract: Preclinical studies and adjuvant trials using bisphosphonates have found them to have an antitumor effect. Although major advances have been made in chemoprevention strategies with selective estrogen receptor modulators and aromatase inhibitors, their use has been fraught with significant adverse effects such as venous thromboembolic events and an increased risk for endometrial cancer. In this context, several recent observational studies have investigated a chemoprevention role for oral bisphosphonates in decreasing risk for breast cancer. This review will aim to summarize these studies and present a critical evaluation of the association between oral bisphosphonate use and breast cancer risk reduction.Keywords: incidence, risk reduction, chemoprophylaxis, alendronate, zoledronate